Harm Avoidance among Journalists in Iraq (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the avoidance of harm among Iraqi journalists and the nature of the avoidance of harm according to gender, journalists, and work (government-private). The research sample consisted of 200 journalists from all cities of Iraq for the academic year 2023-2024 who were chosen intentionally. The researcher adopted the Harm Avoidance Scale (Cloninger & et al., 1994), translated by Qasim (2018) to suit the Iraqi environment, which consists of 30 items. The results showed that the sample has a high level of harm avoidance. There were no statistically significant differences in harm avoidance in terms of gender and work. In light of the research findings, the researcher recommended including harm avoidance among therapeutic interventions to alleviate cognitive and emotional disorders and conducting a study on the ability to avoid harm in predicting various psychological disorders.